2013
DOI: 10.1371/journal.pone.0081330
|View full text |Cite|
|
Sign up to set email alerts
|

Microbiota Dynamics in Patients Treated with Fecal Microbiota Transplantation for Recurrent Clostridium difficile Infection

Abstract: Clostridium difficile causes antibiotic-associated diarrhea and pseudomembraneous colitis and is responsible for a large and increasing fraction of hospital-acquired infections. Fecal microbiota transplantation (FMT) is an alternate treatment option for recurrent C. difficile infection (RCDI) refractory to antibiotic therapy. It has recently been discussed favorably in the clinical and scientific communities and is receiving increasing public attention. However, short- and long-term health consequences of FMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
141
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(164 citation statements)
references
References 65 publications
20
141
0
3
Order By: Relevance
“…The intestinal microbiome of children, especially the very young, is known to differ from adults yet there is very little data characterizing associated microbiome changes with FMT in children. Microbiome changes have been reported in a 20-mo-old boy (28), with decreased diversity of the microbiome prior to FMT, with a relative abundance of Proteobacteria, with increased diversity after FMT with increasing Bacteroidetes; these are similar changes to those previously described in adults (39,42). Additionally, in a case series of older children increased microbiome diversity after FMT for CDI appears to be sustained in those without IBD, however at 6 mo decreases to pre-FMT baseline in those with IBD, suggesting IBD hostrelated mechanisms may modify fecal microbiome diversity (29).…”
Section: Fecal Transplant In Childrensupporting
confidence: 81%
See 2 more Smart Citations
“…The intestinal microbiome of children, especially the very young, is known to differ from adults yet there is very little data characterizing associated microbiome changes with FMT in children. Microbiome changes have been reported in a 20-mo-old boy (28), with decreased diversity of the microbiome prior to FMT, with a relative abundance of Proteobacteria, with increased diversity after FMT with increasing Bacteroidetes; these are similar changes to those previously described in adults (39,42). Additionally, in a case series of older children increased microbiome diversity after FMT for CDI appears to be sustained in those without IBD, however at 6 mo decreases to pre-FMT baseline in those with IBD, suggesting IBD hostrelated mechanisms may modify fecal microbiome diversity (29).…”
Section: Fecal Transplant In Childrensupporting
confidence: 81%
“…In adults, prior to FMT for recurrent CDI, there is decreased bacterial diversity compared to healthy donors (39)(40)(41). After FMT, microbiota diversity increases in fecal samples and microbiome composition shifts towards the healthy donor (39).…”
Section: Fecal Transplant In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] In animal models of LC, portal hypertension and intestinal hypo-mobility lead to bacterial overgrowth in the small bowel and is considered the primum movens of translocation in these models. 30 In a clinical study of 24 patients with liver cirrhosis the bacterial overgrowth was enhanced by portal hypertension, as suggested by animal models.…”
Section: Pathophysiology Of Bsis In Patients With Liver Cirrhosis: Inmentioning
confidence: 99%
“…Previous studies have suggested that patients who develop recurrence have a less diverse community than patients who have stable recovery (12). The idea that restoration of the gut microbiota is necessary to prevent or mitigate recurrence is supported by an Ļ³90% success rate of fecal microbiota transplantation (FMT) (13), and significant recovery of diversity and community membership has been observed following FMT treatment for recurrent CDI (14)(15)(16). Future treatment options have thus concentrated on approaches that aid in recovery of colonization resistance.…”
mentioning
confidence: 99%